Effect of Catfish (Clarias batrachus) Flour and Pre-Gelatinized Red Bean (Vigna angularis) Flour Substitution on the Saturated and Trans Fat Content of Dried Sponge Cake - Dian Maulida Ahsan; Fitriana Mustikaningrum (ScieClouds Publishing, 2026)
Stunting prevention requires not only nutritional intervention but also the development of practical, acceptable, and locally based functional food products for pregnant women. This study aimed to analyze the effect of substituting catfish flour (Clarias batrachus) and pregelatinized red bean flour (Vigna angularis) in dried sponge cake on saturated fat and trans-fat content, while positioning the product as a potential value-added innovation in maternal nutrition management. This study used an experimental design with a Completely Randomized Design consisting of three formulations and two replications. Formula A served as the control with 100% wheat flour, Formula B used 15% catfish flour and 20% pregelatinized red bean flour, and Formula C used 25% catfish flour and 10% pregelatinized red bean flour. Saturated fat and trans-fat contents were analyzed using laboratory fat analysis procedures, and the data were processed using the Kruskal-Walli’s test. The results showed that saturated fat content decreased descriptively in the substitution formulas, with the lowest value found in Formula B at 2.91%, although the difference was not statistically significant (p>0.05). Trans fat content showed a significant difference among formulations (p<0.05), with Formula B producing the lowest value at 16.81%. These findings indicate that the combination of catfish flour and pregelatinized red bean flour, especially Formula B, can improve the lipid quality of dried sponge cake. The product has potential as a healthier local functional food innovation that supports maternal nutrition, food diversification, and stunting prevention strategies. Further sensory, shelf-life, and feasibility studies are needed before commercialization.